Seduction by contract : law, economics, and psychology in consumer markets - Bar-Gill, Oren. (Oxford : Oxford University Press, 2012)
'Seduction by Contract' explains how consumer contracts emerge from market forces and consumer psychology. Consumers' predictable mistakes - they are short-sighted, optimistic, and imperfectly rational - compel sellers to compete by hiding the true costs of products in complex, misleading contracts. Only better law can overcome the market's failure.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Keywords: Consumer contracts; Marketing; Consumers -- Attitudes